The impact of a 'vicious cycle' on the daily functioning of a group of severely obese adults. Issue 5 (14th September 2016) - Howard, M.; Stapleton, T.; Van den Bergh, N.; Yoder, R.; O'Shea, D.
Summary: As the rates of obesity are steadily increasing, the relevance to occupational therapy (OT) is increasing accordingly. There is limited OT‐focused research internationally, particularly relating to the functional and social implications of obesity and none within an Irish context. This was the first research of its kind at a national level and aimed to explore the daily functional difficulties experienced by a group of adults attending an Irish weight management clinic. A mixed methods study design was deployed, and the two phases were combined to form an overall picture of the daily functional difficulties experienced. Of the 26 participants included in the study, 21 completed the quantitative phase, and 19 of those completed the follow‐on qualitative phase. Mean body mass index (BMI) of those involved in the quantitative phase was 52.6 (range 39–69). Of the 21 respondents, nine were partnered, and 10 were unemployed. A large number of participants ( n = 16) were reported to experience comorbidities alongside their weight, and the number of comorbidities experienced varied between one and seven. A significant correlation was found between a greater number of comorbidities and a greater level of functional difficulties and a lower perceived health‐related quality of life. Interestingly, there was no relationship between BMI and both functional difficulty and perceived health status. The presence of a vicious cycle and interdependency between factors was seen to be an over‐riding, dominant theme throughout the qualitative interviews. The issue of a vicious cycle was reinforced in the quantitative measures where community participation in particular was reported to be an area of neglect due to the interaction of emotional difficulties, physiological difficulties, environmental barriers and societal attitudes. The complex interaction and incremental worsening of factors was also seen to be a major barrier to effective implementation of the advice given by the weight management clinic into everyday occupational performance. The findings indicate the complex interaction that exists between the consequences of obesity and their impact on health and well‐being. Understanding of such interactions will have important implications for OT practice as addressing these factors on a continuum rather than in isolation may lead to greater success with weight‐loss interventions and also with occupational re‐engagement.